2016
DOI: 10.1002/hipo.22666
|View full text |Cite
|
Sign up to set email alerts
|

Active place avoidance is no more stressful than unreinforced exploration of a familiar environment

Abstract: Training in the active place avoidance task changes hippocampus synaptic function, the dynamics of hippocampus local field potentials, place cell discharge, and active place avoidance memory is maintained by persistent PKMζ activity. The extent to which these changes reflect memory processes and/or stress responses is unknown. We designed a study to assess stress within the active place avoidance task by measuring serum corticosterone (CORT) at different stages of training. CORT levels did not differ between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…Lastly, while acute stress and electrical stimulation can induce expression of IEGs 1 , 44 , we do not believe this to be a confounding factor as no differences in the number of Arc + cells were observed between mice that received foot shocks during acquisition of the APA task and those that explored with the shock zone turned off, including after repeat exposures. Others have also shown that the mild foot shocks, similar to those delivered in our APA paradigm, do not alter serum levels of the stress hormone corticosterone in mice 36 ; hence, any influence of the acute stress response on Arc + cell numbers in the APA task is thus likely negligible.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Lastly, while acute stress and electrical stimulation can induce expression of IEGs 1 , 44 , we do not believe this to be a confounding factor as no differences in the number of Arc + cells were observed between mice that received foot shocks during acquisition of the APA task and those that explored with the shock zone turned off, including after repeat exposures. Others have also shown that the mild foot shocks, similar to those delivered in our APA paradigm, do not alter serum levels of the stress hormone corticosterone in mice 36 ; hence, any influence of the acute stress response on Arc + cell numbers in the APA task is thus likely negligible.…”
Section: Discussionmentioning
confidence: 72%
“…The basis for this discrepancy is not clear, as the only major difference between the approaches used in this and other studies is the behavioral paradigm. We speculate that constant swimming in the Morris water maze may be more stressful than intermittent foot shocks in the APA task, and that this difference may specifically affect Arc expression in young adult-born granule cells 36 , 54 , 55 . Consistent with this idea, basolateral amygdala activity has been shown to regulate IEG expression in adult-born granule cells 56 ; however, further studies are required to determine whether the Morris water maze is indeed more stressful for mice than the APA task and, if so, whether this is linked to the proportion of young adult-born granule cells that expresses Arc protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to meet the growing sophistication of the learning and memory field and to test the generality of the postulated mechanisms, the toolkit has needed to expand to multiple estimates of memory. It has been especially important to use memory assays that minimize the need for behavioral shaping (a form of learning itself) and the manipulation of other motivational factors, many of which potentially elicit stress and other potential confounds of the molecular basis of memory (Lesburguères et al ., 2016). …”
Section: [Background]mentioning
confidence: 99%
“…Moreover, the results from the present study showed no effects of PEE, even though the same model of exposure was used. The discrepancy between these results may be due to the differing nature of the tasks, where the MWM induces high levels of stress and requires a significant amount of motor activity (swimming), while the APA requires locomotion but does not have the added stress of swimming (Lesburguères et al 2016); perhaps the credit found in ethanol-exposed animals in the MWM was driven by stress and not particularly due to superior learning skills, while the settings on the APA were not challenging enough to uncover an impairment. If the test was to be repeated, the shock strength could be lowered (to reduce stress-driven performance), the shock zone could be smaller and spatial cues shuffled on each day of testing.…”
Section: Effects Of Dvd Deficiency and Pee On Learning And Memorymentioning
confidence: 95%